Copper‐Based Catalysts Supported on Highly Porous Silica for the Water Gas Shift Reaction. Issue 4 (17th February 2016) - Marras, Claudia; Loche, Danilo; Carta, Daniela; Casula, Maria Francesca; Schirru, Manuela; Cutrufello, Maria Giorgia; Corrias, Anna
Abstract: Copper‐based nanoparticles, supported on either a silica aerogel or cubic mesostructured silicas obtained by using two different synthetic protocols, were used as catalysts for the water gas shift reaction. The obtained nanocomposites were thoroughly characterised before and after catalysis through nitrogen adsorption–desorption measurements at −196 °C, TEM, and wide‐ and low‐angle XRD. The samples before catalysis contained nanoparticles of copper oxides (either CuO or Cu2 O), whereas the formation of metallic copper nanoparticles, constituting the active catalytic phase, was observed either by using pre‐treatment in a reducing atmosphere or directly during the catalytic reaction owing to the presence of carbon monoxide. A key role in determining the catalytic performances of the samples is played by the ability of different matrices to promote a high dispersion of copper metal nanoparticles. The best catalytic performances are obtained with the aerogel sample, which also exhibits constant carbon monoxide conversion values at constant temperature and reproducible behaviour after subsequent catalytic runs. On the other hand, in the catalysts based on cubic mesostructured silica, the detrimental effects related to sintering of copper nanoparticles are avoided only on the silica support, which is able to produce a reasonable dispersion of the copper nanophase. Abstract : Don't gather round ! Successful strategies for the design of nanocomposite catalysts for the water gas shift reaction rely on the preparation of copper‐based nanoparticles finely dispersed in highly porous silica matrices (see figure). Different catalytic performances are explained on the basis of different dispersibility and reducibility of copper phases on silica aerogels and templated mesoporous SBA‐16 silicas.